2017
DOI: 10.3892/ol.2017.7047
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of neutrophil to lymphocyte and platelet to lymphocyte ratios for patients with lung cancer

Abstract: As the leading cause of cancer-associated mortality globally among males in 2012, lung cancer is a disease of particular concern. Previously, the neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR) were revealed to be prognostic factors for various types of cancer, including lung cancer. In the present study, a retrospective review was conducted with patients who were diagnosed with lung cancer between January 1, 2000 and December 31, 2005 in the Fourth Hospital of Hebei Medical Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
4
20
0
1
Order By: Relevance
“…The prognosis is better in patients with lower tumor stage than in those with higher stage [ 45 ]. In other types of cancer, a lower tumor stage was associated with lower NLR levels [ 46 , 47 ]. In our study, the subgroup with low tumor stages (I-II) showed higher rate of high NLR than the subgroup with high tumor stages (III-IV) (0.656 versus 0.373).…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis is better in patients with lower tumor stage than in those with higher stage [ 45 ]. In other types of cancer, a lower tumor stage was associated with lower NLR levels [ 46 , 47 ]. In our study, the subgroup with low tumor stages (I-II) showed higher rate of high NLR than the subgroup with high tumor stages (III-IV) (0.656 versus 0.373).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that NLR and PLR were independent prognostic factors in cancer patients [ 26 , 27 ]. However, there are also some studies showing that NLR and PLR were ineffective in predicting the prognosis [ 28 30 ], indicating the prognostic role of NLR and PLR in cancer still need further investigation. They may should be assessed together with other markers due to the confounding factors regulating by inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…According to the inclusion and exclusion criteria, after reviewing duplicates and screening the titles or abstracts, 59 research articles were evaluated. Finally, 20 eligible studies were included [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], with 21 outcomes. The flow chart for the study is shown in Fig 1.…”
Section: Study Searchmentioning
confidence: 99%